AUDIT QUALITY AND FINANCIAL HEALTH: A STUDY OF LEADING INDIAN BANKS - Vishal Patel; Kumar Aditya (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study investigates the relationship between audit quality and financial performance among leading Indian commercial banks from 2015 to 2024. Audit quality is assessed using a composite Audit Committee Score (ACS), developed through a binary scoring method based on 14 parameters that consider regulatory compliance and governance best practices. The research utilizes a panel of nine Nifty Bank Index banks, selected based on consistent data availability throughout the study period. The study is structured around two primary objectives. Firstly, to evaluate the effectiveness of audit committees, mean ACS values were calculated and used to rank the banks. The findings reveal that private sector banks, particularly Kotak Mahindra Bank and Federal Bank, consistently demonstrated higher audit effectiveness compared to their public sector counterparts. Secondly, the research examines the impact of audit quality on financial performance, with Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) as dependent variables. Panel regression analysis, supported by relevant diagnostic tests and model selection criteria, indicates a statistically significant positive effect of ACS on ROA and ROE, while the effect on NIM was positive but not significant. The research underscores the crucial role of efficient audit committees in enhancing profitability and financial control in banks. The study recommends regulatory and institutional measures to further strengthen the structures of audit committees, particularly in public sector banks, in alignment with best governance practices and financial stability.